Victims of Rape and The Legal Protection: Problems and Challenges in The Victimological Studies (Universitas Negeri Semarang, 2023)
Victims of the crime of rape have not received optimal legal protection, even though they have been legally protected through the Law on the Protection of Witnesses and Victims, the Law on Child Protection, or the Law on the Elimination of Domestic Violence. However, the concept of Indonesian criminal law, which focuses more on punishing and deterring criminals, has not been able to accommodate the rights of victims, especially in cases of certain crimes such as rape. In the case of rape, the victim receives an immaterial loss (loss of honor) which is legally difficult to materialize, so that the punishment is limited to imprisonment and a fine which is not sufficient to restore the victim's loss and restore the victim's trauma. This study aims to analyze the protection of victims of rape crime in the perspective of victimology and law. This study uses a normative legal approach, literature review and legal analysis. This study found that the juridical sera, the protection of victims of crime, including victims of rape, has been regulated by the state through several laws. The rights of victims have also been mentioned, ranging from restitution, to recovery of victims' losses and trauma. However, in cases of rape, victims are often dissatisfied with the punishment given to the perpetrators of this crime.